Drug Dealing and Legitimate Self‐Employment - Fairlie, Robert W. (Journal of Labor Economics, 2002)
Theoretical models of self‐employment posit that attitudes toward risk, entrepreneurial ability, and preferences for autonomy are central to the individual's decision between self‐employment and wage/salary work. I provide indirect evidence on this hypothesis by examining the relationship between drug dealing as a youth and legitimate self‐employment in later years using data from the National Longitudinal Survey of Youth. I find that drug dealers are 11%–21% more likely to choose self‐employment than non‐drug‐dealers, all else equal. After ruling out a few alternative explanations, I interpret these results as providing indirect evidence supporting the hypothesis.